From collusion to collective compassion: putting heart back into the neoliberal university. (3rd July 2017) - Mutch, Carol; Tatebe, Jennifer
Abstract: As neoliberal ideology has come to dominate higher education, the roles and relationships of managers, academics and students have changed radically. This article outlines ways in which neoliberalism and its companion ideology, neoconservatism, have impacted on higher education through a move to individualism, managerialism, measurement and accountability. While the context for this article is New Zealand, the experiences will resonate with academics worldwide. Using a conceptual framework highlighting conscious, unwitting and coercive complicity, the authors analyse their experiences of teaching in the neoliberal university. They discuss three themes to emerge from their findings: (a) universities as instruments of neoliberalism; (b) academics as managed subjects; and (c) students as entitled consumers. They conclude by offering examples of ways to resist the competitive and individualising regime by creating a culture of care and compassion.